AI-Assisted Diet or Dietitian? Pilot Comparison of Nutritional Therapy in Decompensated Cirrhosis Patients with Malnutrition - Hilal Toklu Baloğlu (Middle Black Sea Journal of Health Science, 2026)
Objective: This study aimed to evaluate the clinical accuracy and degree of individualization of diets generated by ChatGPT-3.5 for malnourished simulated cases with decompensated cirrhosis. A secondary aim was to quantitatively compare the nutrient composition of diets generated by ChatGPT with individualized medical nutrition therapy plans prepared by a dietitian.Methods: Ten simulated case profiles (five women and five men) representing malnourished individuals with decompensated cirrhosis of different ages and body mass indices were developed. The same clinical and demographic information was provided to both ChatGPT and the same registered dietitian for each simulated case to ensure comparability. ChatGPT and the dietitian independently generated individualized dietary plans and nutrition therapy recommendations. The nutrient composition of all diets was analyzed using the BeBiS nutrition software. Differences between the two approaches were evaluated using the Wilcoxon signed-rank test, with statistical significance set at p < 0.05.Results: Compared with dietitian-generated diets, ChatGPT-generated diets contained significantly higher amounts of protein and a higher percentage of energy derived from protein, whereas carbohydrate content, the percentage of energy from carbohydrates, dietary fiber, plant protein, and potassium were significantly lower, whereas sodium content was significantly higher in the ChatGPT-generated diets (p0.05). Furthermore, seven of the ten simulated cases received identical diets despite having different nutritional characteristics, indicating insufficient dietary individualization.Conclusion: Although ChatGPT can provide general nutrition guidance, it demonstrated important limitations in generating individualized medical nutrition therapy for malnourished simulated cases with decompensated cirrhosis. AI-generated dietary plans should therefore be reviewed and individualized by a registered dietitian before clinical implementation.